PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM @ANAKMAGANG.ID TERHADAP PEMENUHAN KEBUTUHAN INFORMASI LOWONGAN MAGANG (Survei Pada Followers Akun Instagram @Anakmagang.id) - Muhammad Abdul Aziz, (2024)
This study purpose to determine the effect of using social media Instagram @anakmagang.id on fulfilling the need for information about internship vacancies. The source of this research data comes from primary data and secondary data, and the theory used in this research is the uses and gratifications theory. This study used an explanatory type, positivism paradigm, quantitative approach, and a survey method using a Likert scale in the form of a Google Form questionnaire, then distributed to 100 respondents. The population in this study were followers of the Instagram account @anakmagang.id, and the sampling technique used was the Non-Probability Sampling technique (Purposive Sampling) using the Taro Yamane formula. The data analysis technique used is inferential statistics using the SPSS 26 program by conducting validity tests, reliability tests, correlation tests, regression tests, coefficient of determination tests, and hypothesis testing. Based on the results of the correlation test, a value of 0.621 was found, which means that it has a strong correlation level. The results of the regression test found a value of 0.766, which means that if the social media message variable increases by one level, the information needs fulfillment variable will increase by 0.766, the test results of the coefficient of determination found a value of 53.4%, which means that the social media message variable has an influence of 53.4% on the information needs fulfillment variable, the results of the hypothesis test found a value of 10.604, which means t count is greater than t table or there is an influence between variable of social media message to the variable of fulfilling information needs. The results of the study show that the use of Instagram @anakmagang.id social media has an effect on fulfilling the information needs of internship vacancies.